Development of nanostructured nickel reinforced polyacrylamide via frontal polymerization for a reliable room temperature humidity sensor - Chaudhary P.; Maurya D.K.; Sikarwar S.; Yadav B.C.; Dzhardimalieva G.I.; Prakash R. (My University, 2025)
The present paper reports the polymer matrix of Ni(NO3)2(AAm)4·2H2O thin film as an electrical and opto-electronic humidity sensor. For this purpose, films were prepared by spin-coating method to investigate the adsorption/desorption of humidity at room ambient. The sensing element was investigated through X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM) and UV–Vis absorption techniques. XRD exhibited the crystalline nature of the nanomaterial thin film and evaluated average crystallite size was 30 nm. SEM showed highly porous nanostructures of different size distributed throughout the film. Energy band-gap of the film was estimated as 4.034 eV. TEM image showed the nanostructures with the average grain size of 4-21 nm and SAED confirmed the crystalline nature of the material. The film was further employed for two different modes of humidity sensing i.e., impedance-based electrical humidity measurement and transmission based opto-electronic humidity measurement which gave a maximum average sensitivity of 37.79 MΩ/%RH and 1.31 µW/%RH respectively at room temperature. © 2018 Elsevier Ltd